Are users the Next Entrepreneurs? A case Study on the Video Game Industry - Burger-Helmchen, Thierry; Guittard, Claude (Senate Hall, 2008)
Knowledge based-entrepreneurial firms struggle to survive because they have to be simultaneously entrepreneurial on several dimensions. Can these firms rely on users to achieve sufficient efficiency in some entrepreneurial dimensions? To answer this question we drew on the entrepreneurial theories of the firm and on the users/innovator literature. In this work we present the plural entrepreneurship framework and then with a longitudinal case study of a mobile phone videogame firm which relies on users to improve their games we show that the user can significantly enhance the efficiency of the innovation of the firm. We also show that the other important dimensions of the firm behavior (organization, business model) can be significantly improved by the implication of users.
Keywords: plural entrepreneurship|management of innovation|video-game case study